The Clue. Issue 2 (16th March 2017) - Tate, Tyler
Abstract: As I stood outside of Carlos's room, I felt caught on the horns of a dilemma. It seemed impossible to truly "be there" for Carlos without sacrificing my other intern duties. This tension pervaded much of my residency training, as I often found myself spending more time completing chart notes, answering pages, and giving sign out than I did at the bedside with my patients. I knew I had a duty to "do my job"—I could not let my team down. But what about my duty to Carlos, a duty to act on my intuition and try to "get to the bottom" of his illness, if that was even possible? And what about my thirteen other patients? Wasn't I was their doctor as well? I have spent countless hours studying the ethical frameworks for medical rationing. And yet no framework could have told me how to weigh my intuition in that crucial moment of decision‐making, or when it was okay to leave a few notes unfinished in order to have the time to talk with Carlos. Suddenly, I knew what I had to do.